AI – aided translation: An eye on ChatGPT as a tool of Translating Literary Texts - Mai Abdel karim Mohammad Malkawi,; Ayman Altalahin,; Majd Saleem Hussein Abushunar,; Abdullah S. Aldelaa, (Technium Social Sciences Journal, 2025)
The present study aims at analyzing the output of ChatGPT translation of English literary texts into Arabic comparing it to that of other tools like Google Translate and Microsoft Bing. The paper is designed to explore both the efficiency and the pitfalls of the AI – aided ChatGPT when dealing with literary texts mainly poetry. The goal of this paper is to discover whether AI- tools offer precise translation of the examined texts. The approach used is a qualitative approach through which the results and the observations were studied and analyzed.